(untitled) (Tamaddun, 2022)
Studies of teacher-students politeness are presented mostly in direct communicationor face-to-face communication. filling the gap of politeness between teacher and students in online learning is the aim of this study, specifically in one of the very popular educational platforms applied during the Covid-19 pandemic. The platform is Zoom Class. This study applies qualitative research method to describe the phenomenon of the language. This study observed the interaction of 7 zoom classes of English Department students from September to November 2021. The researchers did the analysis on students’ interaction with their lecturer based on the theory of politeness stated by Brown and Levinson. It is found that there are five strategies which 3 of them belong to positive politeness strategies, namely greeting, gratitude, and address term, then negative politeness strategies namely apology and mixing language. The gratitudeis dominantly applied by students with the utterances “thank you” to minimize the threat and maintain the relationship between them. these politeness strategies also used to ensure the effectiveness of online learning interaction as it increases students’ language competence. However, the problem also faced by students and lecturer during the learning process by online learning. Fortunately, the problem could be solved. Thus, this finding contributes to enrich the aspects of politeness interaction in zoom class and provide future researchers to explore politeness in other context.